Non-Communicable Disease Screening Through the Healthy Tent Program in Menunggal Village, Kedamean District, Gresik - Rafli, Muhamamd; Putri, Alvania Medikana (UNUSA Press, 2023)
Non-communicable diseases are diseases that are not transmitted from one individual to another. The most common non-communicable diseases that occur in the community are hypertension, hypercholesterolemia, hyperuricemia, and hyperglycemia. Because the disease is individual, the only way to find the case is to check directly with a health facility. One of the efforts that can be made is with activities in the form of free health checks to screen for certain diseases with simple examinations. This activity was carried out at the Village Hall with the target age of the elderly, namely for those over 45 years old. Participants were gathered in one place and then examined ranging from anthropometry such as height and weight, vital signs such as blood pressure and temperature as well as some simple blood tests such as cholesterol, uric acid and blood sugar. Participants who were found to have abnormal examination values, they were given education in the form of treatment and correct lifestyle information to control the disease or complaints experienced. This activity was quite enthusiastic from the community with the number of participants who participated was 28 people. In the results of the data found, it was found that 6 people with hyperuricemia, 6 people with hyperglycemia, 6 people with hyperglycemia and 1 person with hyperglycemia. Thus, although the examination carried out seems simple, it turns out that it has succeeded in screening some of these non-communicable diseases so that it is expected to be treated early and not continue fatally.